Neurotic Self in Henrik Ibsen’s The Master Builder - Phuyal, Komal Prasad (NPRC Journal of Multidisciplinary Research, 2025)
Background: Henrik Ibsen (1828-1906) derives the dramatic tension from the neurotic self of the protagonist in his seminal play, The Master Builder (1892). The playwright builds on the repressed content of the protagonist: anxiety, phobia, and obsession appear in him, resulting in a neurosis. Methods: This study attempts to interpret the abnormal behavior of the central character through the psychoanalytic lens of Sigmund Freud (1856-1939), who has provided us with a functional model of the id, the ego, and the superego as the three drives in the human mind. Result: Ibsen employs anxiety, phobia, and obsession as the window to examine the inner composition of his personality and critiques the social contradictions that were rising in Norwegian society in the 1880s and the 18890s. Critically approaching the protagonist and the root of his motivation, this paper argues that Halvard Solness suffers from neurosis that manifests through unusual behavior with Ragner, Kaiza Fosli, and Hilde. Conclusion: The family tension that Solness undergoes throughout the play can also be explained through Freudian theoretical design of the repression and lack of sublimation in personality. Novelty: Finally, this paper concludes that anxiety, phobia, and obsession in the protagonist's behavior help us understand the neurotic self, which functions as the central impetus in the play.